New Insights into the Rock Art of Anbangbang Gallery, Kakadu National Park. (17th February 2020) - May, Sally K.; Huntley, Jillian; Marshall, Melissa; Miller, Emily; Hayward, John A.; Jalandoni, Andrea; Goldhahn, Joakim; Johnston, Iain G.; Lee, Jeffrey; O'Loughlin, Gabrielle; May, Kadeem; Sanz, Ines Domingo; et al.
ABSTRACT: This paper presents findings from a recent study of the Anbangbang Gallery in the Burrungkuy (Nourlangie) site complex of Kakadu National Park, Australia. Using new technologies alongside established methods for rock art documentation, we discuss the complexity and uniqueness of Anbangbang Gallery as an icon of Australian rock art. We have taken a comprehensive approach to our investigations, deliberately linking new technologies and scientific analysis with other archaeological and anthropological research methods. In particular, using evidence from a detailed site recording, oral histories, and pXRF analysis, we explore aspects of the site chronology, the nature of painting activity, and the retouching and repainting of earlier imagery. The findings force us to rethink the existing interpretative narrative for Anbangbang Gallery, the motivations behind previously held beliefs relating to recent rock art, and the implications this has had for ongoing conservation work in the region.